(untitled) (Bulletin KNOB, 2022)
The front elevation of the Ridderzaal (Knights’ Hall) in the Binnenhof in The Hague is one of the best-known frontages in the country. The impressive facade was built in around 1295 by Count Floris V as a Schauseite or ‘best side’ of the stately hall. The front elevation and its two towers were recently the subject of building history research. It is known that the elevation underwent major restoration between 1861 and 1900, but the key question explored in this article is to what extent the late thirteenth-century elevation was modified. Our research focused on modifications to the gable and the authenticity of the two flanking towers. A subsequent building history study has revealed that the gable wall line was altered several times during this period, ultimately resulting in a more massive gable. As to the towers, it was previously unclear whether they were part of the original design. Because of their asymmetrical position and different dimensions it was surmised that they had not been built at the same time as the hall and may even have been heightened at a later date. A dendrochronological analysis conducted in 1998 dated the entablatures supporting the steeple to around 1295. However, because seventeenth-century wood was also encountered, it was speculated that the thirteenth-century timber had been recycled. A new analysis of the assembly marks on the entablatures supports the notion that they do indeed date from the building period, which in turn suggests that the current height of the towers is the original height: in other words, both towers were part of the thirteenth-century design.